2009
DOI: 10.1111/j.1365-2184.2009.00584.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cyclin‐dependent kinases by olomoucine and roscovitine reduces lipopolysaccharide‐induced inflammatory responses via down‐regulation of nuclear factor κB

et al.

Abstract: The findings of this study suggest that inhibition of cell-cycle progression is capable of reducing pro-inflammatory responses via down-regulation of NF-kappaB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 36 publications
3
24
0
Order By: Relevance
“…Consistent with these findings, we have reported that flavopiridol, a pan-selective CDK inhibitor, potently inhibits NF-B-dependent gene expression (33). Additionally, murine 264.7 macrophages treated with olomoucine and roscovitine, selective inhibitors of CDK1, -2, -5, and -7, exhibit a reduction in lipopolysaccharide-induced inflammatory responses by down-regulating NF-B-dependent gene expression (42). Taken together, these studies suggest that CDKs regulate NF-B-dependent gene expression by various mechanisms and at multiple steps in the transcriptional activation process.…”
Section: Discussionsupporting
confidence: 47%
“…Consistent with these findings, we have reported that flavopiridol, a pan-selective CDK inhibitor, potently inhibits NF-B-dependent gene expression (33). Additionally, murine 264.7 macrophages treated with olomoucine and roscovitine, selective inhibitors of CDK1, -2, -5, and -7, exhibit a reduction in lipopolysaccharide-induced inflammatory responses by down-regulating NF-B-dependent gene expression (42). Taken together, these studies suggest that CDKs regulate NF-B-dependent gene expression by various mechanisms and at multiple steps in the transcriptional activation process.…”
Section: Discussionsupporting
confidence: 47%
“…R-roscovitine was shown to reduce TNF-α, IL-6 and IL-1β mRNA levels in the RAW 264.7 cell line (19). We expanded these findings with protein measurements of TNF-α and KC in three mouse cell lines relevant for lung inflammatory responses.…”
Section: Discussionmentioning
confidence: 98%
“…Previously, R-roscovitine was shown to reduce COX-2, IL-6, IL-1β and TNF-α mRNA expression levels in LPSstimulated RAW264.7 cells (murine macrophages) (19,28). We set out to investigate the effect of R-roscovitine on protein levels, rather than mRNA expression levels, of inflammatory mediators.…”
Section: R-roscovitine Inhibits Lta-induced Inflammatory Mediator Promentioning
confidence: 99%
See 2 more Smart Citations